Analysis of the Application of Emergency Severity Index Toward Patient Triage Response Time In the Emergency Department: Literature Review - Nesi Nggosual; Anshar Rante; Djusmadi Rasyid; Cici Pratiwi (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Triage is the process of determining the condition of patients at risk of death, potential disability, and worsening patient conditions. Response time is crucial in treating patients quickly and accurately. Objective This literature study aims to analyze the application of the Emergency Severity Index (ESI) Triage to the Triage Response Time in the Emergency Department. Methods: This research employs a literature review study with an analytic method approach that meets the inclusion and exclusion criteria. The search for articles or journals utilizes keywords and Boolean operators to refine the search and select relevant literature. The keywords used include ESI, Triage, Response time,